Arte dos dolmenes do noroeste da Península Ibérica : uma revisão analítica - Sanches, Maria de Jesus (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This text discusses the process of construction-use-closure of decorated dolmens in the northwest of the Iberian Peninsula. The “decoration” is perceived as one of the aspects of collective social negotiation underlying the construction of the monument. In fact, the construction and decoration reflect the maintenance, recreation and alteration of specific memories, identities and ideologies in the Neolithic communities of the region. Each monument contains a specific inner scenography that is anchored in the scenographic, mythographic and ideological traditions of the wider region.